Estudio de pre- factibilidad para la instalación de una fábrica de calzado femenino en la ciudad de Trujillo - Germán González, Dora Elizabeth (2013)
The main objetive this thesis es to evaluate the technical, economic and financial viability from the study of pre-feasibility in order to carry out a female shoe factory in Trujillo. Thus, a market survey was undertaken, as well as a technical study and a financial economic one. In the market survey a projection on the shoe demand was carried out, a prices analysis, data analysis from a survey and a supply analysis. In the technical study the location of the project was determined, the optimal size of the project, materials and supplies availability and also the description of the flow of processes on production. In the financial economic study the income study was determined, costs of investment, manufacturing and operation, finalizing with the economic and financial cash flow of the project. In the same way, the economic viability of the project was demonstrated through the economic indicators as real net value, internal return rate. It was established that the project is technically, economically and financially viable, because the financial and economic indicators validate so VANE = S/. 1,557,856.40, TIRE = 725 % VANF = S/.1,571,047.56, TIRF = 8831 %